Study of modifiable risk factors for asthma exacerbations: virus infection and allergen exposure increase the risk of asthma hospital admissions in children. Issue 5 (29th December 2005) - Murray, C S; Poletti, G; Kebadze, T; Morris, J; Woodcock, A; Johnston, S L; Custovic, A
Abstract : Background: Asthma exacerbation is the most common cause of hospital admission in children. A study was undertaken to investigate the importance of allergen exposure in sensitised individuals in combination with viral infections and other potentially modifiable risk factors precipitating asthma hospital admission in children. Methods: Eighty four children aged 3–17 years admitted to hospital over a 1 year period with an acute asthma exacerbation (AA) were matched for age and sex with two control groups: stable asthmatics (SA) and children admitted to hospital with non-respiratory conditions (IC). Risk factors were assessed by questionnaires and determination of allergen sensitisation, home allergen exposure, pollen exposure, and respiratory virus infection. Results: Several non-modifiable factors (atopy, duration of asthma) were associated with increased risk. Among the modifiable factors, pet ownership, housing characteristics, and parental smoking did not differ between the groups. Regular inhaled corticosteroid treatment was significantly less common in the AA group than in the SA group (OR 0.2, 95% CI 0.1 to 0.6; p = 0.002). A significantly higher proportion of the AA group were virus infected (44%) and sensitised and highly exposed to sensitising allergen (76%) compared with the SA (18% and 48%) and IC groups (17% and 28%; both p<0.001). In a multiple conditional logistic regression (AA v SA), allergen sensitisation and exposure or virus detection alone were no longer independently associated with hospital admission. However, the combination of virus detection and sensitisation with high allergen exposure substantially increased the risk of admission to hospital (OR 19.4, 95% CI 3.7 to 101.5, p<0.001). Conclusions: Natural virus infection and real life allergen exposure in allergic asthmatic children increase the risk of hospital admission. Strategies for preventing exacerbations will need to address these factors.